Role of social mobilization in tackling the resistance to polio eradication program in underserved communities of Aligarh, India - Ansari, M Athar; Khan, Zulfia; Mehnaz, Saira; Shah, M Salman; Abedi, A Jafar; Ahmad, Anees (South East Asia Journal of Public Health, 2014)
Poliomyelitis (polio) is a highly infectious viral disease and mainly affects children under five years of age. The present cross-sectional study was conducted to assess the impact of social mobilization on families resistant to giv-ing polio drops to their children. One round of polio drop administration during September, 2012 was selected ran-domly from total six rounds of Pulse Polio Immunization campaign carried out in the year 2012 in Aligarh, India. Medical interns of the Aligarh Muslim University were trained as social mobilizers by the UNICEF, Rotary Interna-tional trainers and divided into Teams A and B. The teams of social mobilizers visited the households that re-fused to give polio drops to their children because of certain rumors and misguided beliefs. Medical intern tried to convince the family members that polio drops were safe and it did not hurt any religious and cultural sentiments. The total number of resistant families, identified during the house to house outreach activity of Team A was 309. A large number of houses (70.9%) were converted to P houses (houses where children had polio vaccination). Ninety houses (29.1%) remained resistant even after the activity of Team A. These resistant houses were again visited by Team B members. Out of these 90 houses, polio drops were administered in 70 (78.9%) houses. How-ever, after maximum efforts of both the teams, only 19 (21.1%) houses remained extremely resistant. Large numbers of resistant families were converted to P houses where children were administered oral polio drops. However, some of the families remained resistant even after maximum efforts of the teams. These extremely resistant families might be the potent sources of polio infection in the community and they should be followed up strictly. Strategies and polices should be developed to cover all children of the community by assessing the reasons for families resistance to polio drop, examining the past failures/limitations in program implementation, and implementing the effective social mobilizing techniques. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20035 South East Asian Journal of Public Health Vol.3(2) 2013: 23-29